Material and subjective wellbeing of Malaysian household: a comparative analysis / Farah Shazlin Johari, Hamidah Muhd Irpan and Mohamed Saladin Abdul Rasool - Johari, Farah Shazlin; Muhd Irpan, Hamidah; Abdul Rasool, Mohamed Saladin (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The concept of wellbeing has attracted many researchers in multi-disciplines. Objective wellbeing particularly focuses on quality of life indicators such as material resources (material wellbeing). On the other hand, subjective wellbeing emphasizes on subjective experiences and judgments of individuals in their lives in better ways. In fact, numerous studies have shown several determinants associated with material and subjective wellbeing. To gain better understanding, the purpose of this study is to explore the impact of demographic factors, including age, gender, income, education, and health status on both material and subjective wellbeing among Muslim households. This cross-sectional study was conducted in Alor Gajah, Melaka with the second highest score of Malaysian Wellbeing Index 2016. By using self- administered questionnaires, the present study employed non-proportionate random sampling involving 149 Muslim households. The findings revealed that demographic factors are associated with material and subjective wellbeing.